Social and Educational Exclusion of Roma in Macedonia with Focus on Roma Children on the Street - Bogoevska, Natasha; Trbojevik, Svetlana (Mediterranean Journal of Social Sciences, 2012)
Social and Educational Exclusion of Roma in Macedonia with Focuson Roma Children on the Street